Adult Intra-Thoracic Kidney: A Case Report of Bochdalek Hernia - Valeria Fiaschetti; Luca Velari; Eleonora Gaspari; Roberta Mastrangeli; Giovanni Simonetti (Case Reports in Medicine)
Introduction. Bochdalek hernia is a congenital posterior lateral diaphragmatic defect that allows abdominal viscera to herniate into the thorax. Intrathoracic kidney is a very rare finding representing less than 5% of all renal ectopias with the least frequency of all renal ectopias. Case Presentation. We report a case of a 62-year-old man who had a left thoracic kidney associated with left Bochdalek hernia. Abdominal X-ray and chest X-ray revealed dilated loops of the colon above left hemidiaphragm. Abdominal ultrasound (US) showed the right kidney with many fluid and esophytic cysts; left kidney was unfeasible to study because of the impossibility to find it. Computed Tomography (CT) basal scan demonstrated a left-sided Bochdalek hernia with dilatated colon loops and the left kidney within the pleural space. Magnetic Resonance (MR) confirmed a defect in left hemidiaphragm with herniation of left kidney, omento, spleen and colon flexure, and intrarotation with posterior hilum on sagittal plane. Conclusion. The association of a Bochdalek hernia and an intrathoracic renal ectopia is very rare, that pose many diagnostic and management dilemmas for clinicians. Our patient has been visualized by CT and MR imaging. A high index of suspicion can result in early diagnosis and prompt intervention with reduced morbidity and mortality.